Long chalcogen-chalcogen bonds in electron-rich two and four center bonds: combination of π- and σ-aromaticity to a three-dimensional σ/π-aromaticity - Gleiter, Rolf; Haberhauer, Gebhard (The journal of organic chemistry, 2014)
Quantum chemical calculations were carried out by applying density functional theory to study the two center-three electron (2c-3e) bonds between the sulfur centers of cyclic dithioethers. Calculated were the S-S distance, the stabilization energy, and the energy of the σ → σ* transition. The extension of the calculations to two (2c-3e) bonds in one molecule shows that a rearrangement to one σ bond and two lone pairs on sulfur is usually more favorable. Exceptions are [H2S2+]2, the dimer of the 1,2-dithia-3,5-diazolyl radical (27a), the dimer of the 1,2,4-trithia-3,5-diazolyl radical cation (26a2+), and its Selena congeners and derivatives. In the case of [H2S2+]2, the (4c-6e) bond between the chalcogen centers is a good description of this dimer. To describe the binding situation in the dimer 26a2+ and 27a, the concept of a “simple” (4c-6e) bond was extended. Our calculations reveal a strong σ-aromaticity within the plane of the four sulfur centers in addition to a strong π-conjugation within the five-membered rings. The whole phenomenon can best be described as a three-dimensional σ/π-aromaticity within the 14π dimers.
Gesehen am 30.07.2020